Multilingualism and developmental language disorder in Southeast Asian speech-language pathology practice: An international survey. - Smith, Giuditta; Verdon, Sarah Elizabeth; Chu, Shin Ying; Razak, Rogayah A.; Chow, Deborah; Rusli, Yazmin A.; Aziz, Mohd Azmarul A.; Pham, Ben; Pratomo, Hafidz Triantoro Aji; Garraffa, Maria (International Journal of Speech-Language Pathology, 2026)
Purpose: This study aims to explore the current practices and challenges faced by speech-language pathologists in three Southeast Asian countries (Malaysia, Indonesia, and Vietnam) in assessing and treating multilingual children with developmental language disorder. Method: A survey was designed and administered to 110 speech-language pathologists across Malaysia, Indonesia, and Vietnam. The survey contained 60 questions on current practices and knowledge of existing resources for assessing and treating multilingual children with developmental language disorder. Data were analysed to identify relationships between practices and demographic variables including country of origin, years of service, and speech-language pathologists' multilingual status. Result: Current practices reveal little knowledge and/or use of standardised tests for developmental language disorder across countries, but relatively high self-perceived competence when working with multilingual clients for Indonesia and Malaysia. However, several challenges were perceived across the board in practice with multilingual children, including socioeconomic challenges (i.e. costs involved for families and social status), insufficient training on the relevant topics, and limited access to appropriate tools and resources in their current practice. Conclusion: Findings suggest the need for training and appropriate assessment tools to ensure the adoption of evidence-based service delivery for multilingual caseloads, minimising misclassification of developmental language disorder and boosting confidence levels in speech-language pathologists in Southeast Asia.